Practices enacted by Nepal Open University for equity and access: a qualitative study. (3rd July 2022) - Khanal, Jeevan; Ghimire, Subekshya
ABSTRACT: This article discusses the practices followed by the youngest open university of South Asia and the only open university of Nepal for access and equity through online teaching and learning. Key initiatives that the university has undertaken in this regard are explored to understand how practices and strategies are applied by this higher education institution to provide citizens with equity and access. The findings of this study may contribute to the development of higher education policies, especially in low-income countries such as Nepal.